Dark septate fungal endophytes from a tallgrass prairie and their continuum of interactions with host plants - Mandyam, Keerthi (Kansas State University, 2009)
Dark septate endophytes (DSE) are darkly pigmented microfungal ascomycetes commonly observed in the healthy plant roots. Studying the functional roles of DSE is challenging as fundamental information about their identity, nutritional requirements, host range or host preference are lacking. Objective 1: root colonizing fungi were isolated from Konza plants roots and DSE fungi were identified by testing Koch’s postulates using leek plants. Periconia macrospinosa and Microdochium sp., were identified as DSE as they produced microsclerotia and chlamydospores in the root cortex. Select DSE were tested for their enzymatic capabilities and ability to utilize nitrogen sources: fungi tested positive for amylase, cellulase, polyphenol oxidases and gelatinase. Periconia isolates utilized organic and inorganic nitrogen suggesting facultative biotrophic and saprotrophic habits. Objective 2: a Microdochium isolate and three Periconia isolates were screened on 16 plant species (six native grasses and forbs, four crops) in a resynthesis system to test host range. DSE colonized all plant species, albeit to varying degrees. Host biomass and nutritional levels to DSE colonization varied within and among host species confirming the broad host range. Based on % responsiveness to DSE colonization, a metric similar to ‘mycorrhizal dependency’, grasses responded positively, while forbs and crops responded negatively. To test this observed ‘host preference’ under natural conditions, Konza roots from seven grass and nine forb species were surveyed for DSE colonization. Grasses hosted 50% greater DSE than forbs, supporting the broad host range and host preference of DSE fungi. Objective 3: three conspecific Arabidopsis ecotypes, Col-0, Cvi-0 and Kin-1 were inoculated with 25 P. macrospinosa isolates in resynthesis system. The three ecotypes responded differently to inoculation: Col-0 and Cvi-0 responded negatively, while Kin-1 response was neutral. Despite the negative or neutral response, each ecotype responded positively to one or two isolates. The outcomes were along the mutualism-parasitism continuum precluding an unambiguous assignment to any particular life-style. This study shows that the outcomes along this continuum are dictated by host and fungal genotypes. However, the more important question about their function remains. Additional studies with Arabidopsis microarrays are likely to provide unique insights into the potential roles of DSE.
Keywords: Arabidopsis thaliana; Microdochium sp.; Periconia macrospinosa; mutualism-parasitism continuum; tallgrass prairie; Biology, Ecology (0329)